Riboflavin-induced photodegradation of tryptophan in sodium sulfosuccinate (AOT)-iso-octane-water - Pérez, Hugo Alejandro (2011)
Flavins play an important role in photosensitized reactions that include a wide range ofelectron donor substrates, such as amino acids. In aqueous solutions, triplet state offlavins reacts with amino acids such as Cys, Trp and Tyr with bimolecular quenchingconstants between 1-10109 M-1 s-1 [1]. In aerobic conditions, the flavin photosensitizedoxidation of aminoacids was attributed to H2O2 produced by dismutation of O2•-, generated by the interaction of O2 with the triplet of the flavins and/or radical speciesformed by flavin triplet reaction with the aminoacids [2,3].However, to our knowledge, there are few studies about flavin-photosensitizedoxidation of amino acid in microenvironments which mimic biological systemcompartmentalization. In this work we study the riboflavin (Rf)-mediated reaction oftryptophan in nanodroplets made of sodium sulfosuccinate (AOT)-iso-octane-water bycontinuous blue-LED (460 nm) and laser pulsed (355 nm) photolysis, using bothstationary and dynamic absorption and emission spectroscopies.